Earthquake/Tsunami‐Linked Imprints in the Equatorial F Region Zonal Plasma Drifts and Spatial Structures of Plasma Bubbles. Issue 1 (5th January 2019) - Gurram, P.; Kakad, B.; Ravi Kumar, M.; Bhattacharyya, A.
Abstract: We report preseismic and postseismic distinct features observed in equatorial ionospheric F  region in Indian longitude during two major earthquakes that occurred on 28 March 2005 ( M w =8.6) and 26 December 2004 ( M w =9.1) with epicenters near Sumatra, Indonesia. We used spaced receiver scintillation observations on a 251‐MHz signal transmitted from a geostationary satellite and recorded at dip equatorial station Tirunelveli, which is ≈2, 200 km away from the epicenter of these earthquakes. On 28 March 2005, we noticed significant enhancement (≈88.5 m/s) in F  region zonal plasma drift as compared to their seasonal quiet time drifts, 20 min prior to the start of earthquake. This implies the presence of additional vertically downward electric field of approximately 3 mV/m, which is linked with the earthquake mechanism. It is unusual because so far we have not encountered such feature on either magnetically quiet or disturbed days. Spatial scales associated with equatorial spread F irregularities generated in the postsunset hours on this earthquake day are considerably smaller. It suggests that the earthquake‐linked electric field influenced the structuring and evolution of equatorial spread F irregularities on this earthquake day. Another earthquake that occurred on 26 December 2004 triggered a tsunami. We noticed that the earthquake‐ and tsunami‐linked effects in the F  region plasma drifts are distinctly observed even 18.5 hr after the earthquake. Key Points: Large F region zonal plasma drifts are observed 20 min prior to the earthquake at 2, 200 km away from epicenter Earthquake‐linked strong vertical downward electric field of 3 mV/m is present in the F region on 28 March 2005 Tsunami‐ and earthquake‐linked effects on F region zonal plasma drifts persist even 18.5 hr after the earthquake on 26 December 2004